2022
DOI: 10.3390/ijgi11010059
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into the Coupled Grain–Disaster–Economy System Based on a Multilayer Network: An Empirical Study in China

Abstract: Natural disasters occur frequently causing huge economic losses and reduced grain production. Therefore, it is important to thoroughly explore the spatial correlations between grain, disaster, and the economy. Based on inter-provincial panel data in China in 2019, this study integrates complex network and co-occurrence theory into a coupled grain–disaster–economy (GDE) multilayer network, which provides a new perspective to further explore the spatial correlation between these three systems. We identify the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…By comparing the strength values of spatial correlation, it is found that coastal cities have more signi cant in uence, and they play a positive role in improving the overall coupling level of Fujian Province through their advantages in sports facilitiesand high-level integration with the ecological environment. In addition, due to their proximity, it is conducive to forming a cross-provincial joint development model, which promotes the cross-regional coupling development of sports facilities and ecological environment in the entire region (Qu et al, 2022). Furthermore, the spatial correlation strength of coupling coordination between Sanming and Nanping is also at a relatively high level.…”
Section: Spatial Correlationmentioning
confidence: 99%
“…By comparing the strength values of spatial correlation, it is found that coastal cities have more signi cant in uence, and they play a positive role in improving the overall coupling level of Fujian Province through their advantages in sports facilitiesand high-level integration with the ecological environment. In addition, due to their proximity, it is conducive to forming a cross-provincial joint development model, which promotes the cross-regional coupling development of sports facilities and ecological environment in the entire region (Qu et al, 2022). Furthermore, the spatial correlation strength of coupling coordination between Sanming and Nanping is also at a relatively high level.…”
Section: Spatial Correlationmentioning
confidence: 99%